Development and characterization of tetraglycidyl epoxy reinforced inorganic hybrid nanomaterials for high performance applications. (September 2016) - Duraibabu, D; Alagar, M; Kumar, S Ananda
In the present work, tetraglycidyl 1, 4′-bis (4-amine-phenoxy) benzene (TGBAPB) epoxy resin has been developed using 1, 4′-bis (4-amine-phenoxy) benzene and epichlorohydrin. The amine-functionalized nanoalumina (F-nAl) was prepared using 3-aminopropyltriethoxysilane. TGBAPB epoxy resin was further reinforced with different weight percentages (1–5 wt%) of F-nAl and were cured with 4, 4′-diaminodiphenylmethane. Thermal and thermomechanical behavior of TGBAPB epoxy matrix and nanocomposites were studied using thermogravimetric and differential scanning calorimetric analyses. The surface morphology of epoxy nanocomposites was examined using transmission electron microscopic, scanning electron microscopic, and atomic force microscopic studies respectively. Data obtained from mechanical and thermal studies/analysis indicate that these nanocomposites could be used as high-performance materials for varied advanced industrial and engineering applications.